AUDITORY BEHAVIORAL RESPONSES OF PRETERM INFANTS FOR ENVIRONMENTAL SOUNDS AT HOME - MS. SRUTHI S G; DR. C S VANAJA (The Bioscan, 2025)
Aims: The study compared the auditory behavioral responses reported by mothers of 3-month term infants with those of preterm infants matched for corrected age, as well as with those of preterm infants matched for chronological age. The research was designed to understand auditory responsiveness in a naturalistic home environment. Material and Methods: This was a comparative, cross-sectional study with 90 participants, mothers of 3-month term infants (Group 1), mothers of preterm infants with corrected age of 3 months (Group 2), and mothers of preterm infants with chronological age of 3 months (Group 3). A semi-structured interview was conducted to collect information on mothers' observations of their infants' reactions to a list of 10 common household sounds. The Chi-Square test of homogeneity and Fisher's exact tests were used to check the objectives of the study. Results: Results of Groups 1 differed significantly from those of Group 2, and 3 for responses observed commonly for 4 out of 10 environmental sounds. A greater proportion of mothers of term infants observed responses compared to mothers of preterm infants. However, a significant difference was observed for five types of responses when mothers of term infants were compared with mothers of chronologically age-matched preterm infants. Conclusion: Term infants exhibit responses to a wider number of sounds when compared to preterm infants of the same age. The results emphasize the importance of using corrected age while assessing preterm infants. The maternal observations can be useful in complementing objective assessments of the auditory system. This is especially helpful in countries like India, where newborn hearing screening is not yet universally implemented. KEYWORDS PRETERM INFANTS; AUDITORY DEVELOPMENT; BEHAVIORAL RESPONSES; MATERNAL REPORTS; CORRECTED AGE; ENVIRONMENTAL SOUNDS